Korps Mobile Brigade dalam Mengatasi Masalah DI/TII Jawa Barat (1950-1962) - Alia Widara Putri; Ayi Budi Santosa (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
The research examine about Mobile Brigade Corps’ contribution in overcoming the West Java’s DI/TII affairs. The background of this research is because as a police troops, Mobile Brigade Corps contribute in overcoming one of the domestic security intruption problems that happened in Indonesia in the 1950’s decade, namely West Java’s DI/TII. However, that contribution from Mobile Brigade Corps is unpopular. Then, the main question in this research is how is the contribution of the Mobile Brigade Corps in overcoming the West Java’s DI/TII affairs. The method used in this research was a historical research method, with four research steps, namely heuristics, criticsm, interpretation, and historiography. The research technique used for collected the data was literature and documentation study. Based on this research’s result, West Java was in emergency state (SOB)/danger situation in the 1950’s deacade, it was because at that time, the security condition in West Java was worsed due to the domestic security intruption problem, caused by West Java’s DI/TII. Mobile Brigade Corps involved in overcoming the West Java’s DI/TII affairs because at that time, Djawatan Kepolisian Negara was involved in the task of overcoming that West Java’s DI/TII for seconded to Tentara Teritorium III/Siliwangi, Mobile Brigade Corps used because it’s the paramilitary troops from Djawatan Kepolisian Negara. The efforts from Mobile Brigade Corps were formed the Ranger Troops and mobilized Mobile Brigade Coprs’ troops, including the Ranger Troops in domestic security operation to overcoming the West Java’s DI/TII affairs.